2019
DOI: 10.5455/aim.2019.27.158-161
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Corrected QT (QTc) Dispersion Value as a Predictor for Estimation of Neonatal Mortality in Pre-Term Neonates

Abstract: Introduction:Electrocardiographic (ECG) corrected QT (QTc) interval and dispersion were used as prognostic variables in adult patients and limited studies showed the relationship between QTc prolongation and dispersion with some clinical situations in newborn babies.Aim:In the present study, we compared the electrocardiographic (ECG) variables such as QTc interval and dispersion of healthy full-term and pre-term neonates with those who suffered from non-cardiac illnesses.Methods:This prospective cohort study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As the QTc interval is a safety marker when medicines are administered in ill preterm and term newborns, it is important to document whether illness itself prolongs the QTc interval. A study by Shabestari et al [ 36 ] provided data on the QTc interval in 127 healthy preterm and term neonates versus ill preterm and term neonates. The types of illnesses are provided in Table S8 (‘covariates’).…”
Section: Resultsmentioning
confidence: 99%
“…As the QTc interval is a safety marker when medicines are administered in ill preterm and term newborns, it is important to document whether illness itself prolongs the QTc interval. A study by Shabestari et al [ 36 ] provided data on the QTc interval in 127 healthy preterm and term neonates versus ill preterm and term neonates. The types of illnesses are provided in Table S8 (‘covariates’).…”
Section: Resultsmentioning
confidence: 99%
“…He divided a population of 114 neonates in three cohorts from respectively 31-34 weeks, 34-37 weeks and >37 weeks. Data showed that neonates >37 weeks had a shorter QTc interval on day one to three than preterm (31)(32)(33)(34) neonates and a shorter interval from day two to four than preterm (34)(35)(36)(37) neonates [22]. Thomaidis et al confirmed this limited longer QTc interval in preterms when compared to the fifth day of life in term versus preterm neonates.…”
Section: Early Neonatal Lifementioning
confidence: 97%
“…Those 11 cases had significantly higher QTc values than the other ill term neonates. It seems that the QTc interval is associated with mortality in preterm ill neonates, but no cut-off values were determined [36].…”
Section: Illnessesmentioning
confidence: 99%
“…While historically collected and recorded in a manual fashion, the advent of bedside monitors now provides for the automated collection of vital sign data, in particular that of heart rate, where measures of stability/variability have repeatedly been to be valuable metrics in assessing patient outcomes 11–13 . Continuous monitoring devices and telemetry systems now link directly to a patient's electronic medical record and can autopopulate this document.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…While historically collected and recorded in a manual fashion, the advent of bedside monitors now provides for the automated collection of vital sign data, in particular that of heart rate, where measures of stability/variability have repeatedly been to be valuable metrics in assessing patient outcomes. [11][12][13] Continuous monitoring devices and telemetry systems now link directly to a patient's electronic medical record and can autopopulate this document. Yet, despite the continuous stream of data made available through these monitors; a patient's chart often reflects only a subset of this information with a series of heart rate snapshots recorded throughout a hospitalization.…”
Section: Implications For Clinical Practicementioning
confidence: 99%